Design and Simulation of an Ultra-Wide Field Optical Coherence Tomography Retinal Imaging System - Shanshan Liang (MDPI AG, 2021)
Peripheral retinal imaging is a unique approach for assessing and monitoring ocular diseases. In this paper, we proposed a design for an optical coherence tomography system to accomplish ultrawide field (>120°) retinal imaging without montages. Scanning of the sample arm was achieved via two ellipsoidal mirrors. The optical design software Zemax and an eye model were used to estimate the inherent aberrations in the system and the optical performance of retinal imaging. Simulation results of the aberrations in the designed system indicated that the designed system can achieve an unprecedented imaging field of view (FOV) while maintaining acceptable resolution without sacrificing the working distance. This work suggests that ultrawide field optical coherence tomography retinal imaging is achievable, which is highly important for the diagnosis and treatment of ocular—especially peripheral—retinopathy.